2018
DOI: 10.1073/pnas.1719309115
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation mediates ventricular chamber maturation through repression of Hippo signaling

Abstract: During development, ventricular chamber maturation is a crucial step in the formation of a functionally competent postnatal heart. Defects in this process can lead to left ventricular noncompaction cardiomyopathy and heart failure. However, molecular mechanisms underlying ventricular chamber development remain incompletely understood. Neddylation is a posttranslational modification that attaches ubiquitin-like protein NEDD8 to protein targets via NEDD8-specific E1-E2-E3 enzymes. Here, we report that neddylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 69 publications
(98 reference statements)
2
93
1
Order By: Relevance
“…However, whether F-box proteins mediate the degradation of rEag1 has not been reported. In addition, CUL7 participates in Mst1 ubiquitination to induce YAP signaling and cardiomyocyte proliferation 29 . Wang et al identified a signaling pathway controlling cell migration and placental development involved in the progression of 3-M dwarfism.…”
Section: Cul7 Substrate Proteins In Development and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether F-box proteins mediate the degradation of rEag1 has not been reported. In addition, CUL7 participates in Mst1 ubiquitination to induce YAP signaling and cardiomyocyte proliferation 29 . Wang et al identified a signaling pathway controlling cell migration and placental development involved in the progression of 3-M dwarfism.…”
Section: Cul7 Substrate Proteins In Development and Cancermentioning
confidence: 99%
“…Five cellular proteins have been previously recognized as substrates of the CUL7 E3 ligase: cyclin D1 16 , insulin receptor substrate (IRS-1) 22 , hematopoietic progenitor kinase 1 (HPK1) 23 , Golgi reassembly-stacking protein 65 (GRASP65) 24 , and TBC1 domain family member 31 (TBC1D31) 25 . Recently, additional proteins have been implicated in the degradative process of the CUL7 E3 Ub ligase: histone H2B-like (H2B) 26 , Mof4 family associated protein 1 (MRFAP1) 27 , AID 20 , caspase-8 28 , macrophage stimulating 1 (Mst1) 29 , and pleckstrin homology like domain family B member 2 (LL5β) 30 . Interestingly, several proteins, such as p53 12 , 31 , 32 , SV40 T antigen 33 35 , glomulin (GLMN) 36 , PARC 37 , 38 , obscurin-like 1 (OBSL1), and coiled-coil domain containing 8 (CCDC8) 39 , have been shown to interact with CUL7, but this interaction does not affect their stability, suggesting that the CUL7 E3 ligase may perform a proteolytic function and also play a non-proteolytic role.…”
Section: Introduction Of the Cul7 E3 Ligasesmentioning
confidence: 99%
“…We (46) recently identified an essential role for neddylation in cardiac development and maturation. We demonstrated that neddylation is highly active in embryonic and fetal hearts but is developmentally downregulated in adult hearts.…”
Section: Introductionmentioning
confidence: 99%
“…They also show Poly-SUMOylation is required for OTUB2 to interact with and deubiquitinate YAP/TAZ [49]. Since, Zou et al shows NEDD8 substrate Cul7 acts as a ubiquitin ligase to promote Mst1 degradation, thereby activating YAP signaling and cardiomyocyte proliferation [58]. All these imply OTUB2 may function in cardiac morphogenesis.…”
Section: Otub Subfamily (Otub1 and Otub2)mentioning
confidence: 97%